Comparative Foliar Epidermal Studies in Andropogon Gayanus (Kunth) and Andropogon tectorum (Schum & Thonns) in Nigeria - Folorunso, Abayomi Ezekiel; Olaniyan, Ojuolape Funmilola (2014)
The foliar epidermal studies were carried out on Andropogon gayanus and Andropogon tectorum with the aim of determining the patterns of variation in their epidermal characteristics and assessing their value in species identification and classification. Adaptive and endemic characters that may be useful in the identification of the savanna species (A. gayanus) are long cells longer in length and width; straight anticlinal wall. Typical characters of the genus are important in the identification and classification of the genus; these are cell wall largely thick and straight, stomata amphistomatic, papillae largely numerous and uniform in size.